Condition monitoring of truss bridges with relative displacement sensors - Li, Jun; Hao, H.; Inman, B. (2015)
This paper investigates the feasibility and sensitivity of a recently developed relative displacement sensor for the condition monitoring of steel truss bridges. The developed sensor is an innovative new design offering some advantages and unique features, and is a much easier and cheaper method of structural health monitoring due to the simplicity of its direct measurement of relative displacement with no need for a stable reference point. To investigate the potential applications to structural joints condition monitoring, an experimental steel truss bridge model is farbricated and installed with the developed sensors to detect realtive displacement changes in joint connections. The dynamic measurements are analyzed by using a time frequency analysis method, i.e. continuous wavelet transform, which is a well-practiced signal processing technique to identify a change in structural conditions. The sensitivity range of the developed sensor is also investigated to see how sensitive the sensor is to identify the local bolt damage.